Intravitreal Therapy Against the Complement Factor C5 Prevents Retinal Degeneration in an Experimental Autoimmune Glaucoma Model - Sabrina Reinehr; Sara C. Gomes; Caroline J. Gassel; M. Ali Asaad; Gesa Stute; Marc Schargus; Marc Schargus; H. Burkhard Dick; Stephanie C. Joachim (Frontiers Media S.A., 2019)
In glaucoma, studies revealed an involvement of the complement system. In an experimental autoimmune glaucoma model, immunization with an optic nerve homogenate antigen (ONA) led to retinal ganglion cell (RGC) loss, while intraocular pressure (IOP) remained unchanged. Here, we investigated the therapeutic effect of a complement system inhibition in this model. Hence, rats were immunized with ONA and compared to controls. In one eye of the ONA animals, an antibody against complement factor C5 was intravitreally injected (15 μmol: ONA+C5-I or 25 μmol: ONA+C5-II) before immunization and then every two weeks. IOP was measured weekly. After 6 weeks, spectral-domain optical coherence tomographies (SD-OCT), electroretinograms (ERG), immunohistochemistry, and quantitative real-time PCR analyses were performed. IOP and retinal thickness remained unchanged within all groups. The a-wave amplitudes were not altered in the ONA and ONA+C5-I groups, whereas a decrease was noted in ONA+C5-II animals (p < 0.05). ONA immunization provoked a significant decrease of the b-wave amplitude (p < 0.05), which could be preserved in ONA+C5-I, but not in ONA+C5-II animals. ONA animals showed a loss of RGCs (p = 0.001), while ONA+C5-I and ONA+C5-II retinae had similar cell counts as controls. A significant downregulation of apoptotic Bax/Bcl2 mRNA was noted in ONA+C5-I retinae (p = 0.02). Significantly more C3+ and MAC+ cells were observed in ONA animals (p < 0.001). The amount of C3+ cells in both treatment groups was significantly increased (p < 0.01), while the number of MAC+ cells in the treated retinas did not differ from controls. The number of activated microglia cells remained unchanged in ONA animals, but was increased in the treatment groups (p < 0.05). Recoverin+ cells were diminished in ONA animals (p = 0.049), but not in treated ones. Rho mRNA was downregulated in ONA and in ONA+C5-II retinas (both p = 0.014). Less opsin+ cones were observed in ONA animals (p = 0.009), but not in the treated groups. Our results indicate that the C5 antibody inhibits activation of the complement system, preventing the loss of retinal function as well as RGC, cone bipolar, and photoreceptor loss. Therefore, this approach might be a suitable new treatment for glaucoma patients, in which immune dysregulation plays an important factor for the development and progression of glaucoma.